Acceleration of Marketing Digitalization Towards Independent MSMEs - Bernadin Dwi Mardiatmi; Henki Bayu Seta; Jenji Gunaedi Argo (Indonesian Journal of Society Development, 2023)
The acceleration of Micro, Small, and Medium-Sized Enterprises (MSMEs) are undergoing marketing digitalization in order to boost market access and competitiveness. Through the use of creative marketing techniques, MSMEs can be encouraged to become more independent and powerful. Through the three pillars of the MSME Development Program—increasing output, cutting costs, and growing the market. One of the development's applications program is through the UMKM Digitalization Program. Using online platforms that can be accessed over the internet, such as social media, websites, blogs, online adverts, and the like, online marketing aims to promote items. The growth in internet users globally is a market potential for MSMEs to be used as much as possible to sell their products. 30 (thirty) MSMEs in Cinere Depok District, West Java were the targets of this exercise in order to benefit from this digital era as an opportunity to optimize the achievement of online-based sales targets. The purpose of this activity is to provide basic knowledge of the importance of digital marketing, branding, as well as simple brand analysis and development. The method used is through digital-based marketing assistance, through the practice of creating Facebook and Tokopedia accounts. The results of this activity through the pre-test and post-test showed an increase in understanding of marketing digitalization as evidenced by an increase in the post-test score, which was higher than the average pre-test score of 5.40 to 7.10